2024
DOI: 10.1002/adfm.202400980
|View full text |Cite
|
Sign up to set email alerts
|

Graphoepitaxially Side‐By‐Side Nanofins Along Atomic Terraces for Enhancement‐Mode FinFETs with 108 On/Off Ratio

Jinyou Xu

Abstract: The innovation of 3D FinFETs using top‐down silicon nanofins represents a significant advancement toward scaling down microchip process nodes to the cutting‐edge 3‐nm level. While bottom‐up semiconductor nanofins also hold promise as building blocks for FinFETs, their controlled growth remains challenging. Drawing inspiration from the guided roots along brick gaps, this study shows that the aligned atomic terraces on an annealed miscut LaAlO3 surface can trigger an exceptional graphoepitaxial effect, encouragi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…35 Xu et al reported that the horizontally grown CdS nanowalls with graphoepitaxy exhibited better field effect transistor performance than the planar CdS transistors in enhancement mode due to their unique features of guided nanowalls. 24,28 To the best of our knowledge, controlling the growth direction of 1D MoO 2 nanostructures by tailoring surface properties of substrates has not been reported. properties of directionally grown 1D MoO 2 nanostructures, including in situ conductivity, polarized Raman, etc., need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Xu et al reported that the horizontally grown CdS nanowalls with graphoepitaxy exhibited better field effect transistor performance than the planar CdS transistors in enhancement mode due to their unique features of guided nanowalls. 24,28 To the best of our knowledge, controlling the growth direction of 1D MoO 2 nanostructures by tailoring surface properties of substrates has not been reported. properties of directionally grown 1D MoO 2 nanostructures, including in situ conductivity, polarized Raman, etc., need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…They later achieved the guided growth of millimeter-long GaN nanowires along the nanogrooves of the annealed M-plane (101̅0) sapphire . Up to now, the generality of graphoepitaxial growth has been widely demonstrated in the horizontally oriented growth of various 1D inorganic (e.g., ZnTe, ZnSe, ZnO, CdSe, and CdS) or organic (e.g., metal phthalocyanines, Alq3) nanowires on various substrates (such as SiC, quartz, and spinel). ,,, …”
Section: Introductionmentioning
confidence: 99%